2012
DOI: 10.3390/nu4122097
|View full text |Cite
|
Sign up to set email alerts
|

Food Sources of Energy and Nutrients among Adults in the US: NHANES 2003–2006

Abstract: Identification of current food sources of energy and nutrients among US adults is needed to help with public health efforts to implement feasible and appropriate dietary recommendations. To determine the food sources of energy and 26 nutrients consumed by US adults the 2003–2006 National Health and Nutrition Examination Survey (NHANES) 24-h recall (Day 1) dietary intake data from a nationally representative sample of adults 19+ years of age (y) (n = 9490) were analyzed. An updated USDA Dietary Source Nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
247
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(259 citation statements)
references
References 37 publications
12
247
0
Order By: Relevance
“…This dietary pattern is very different from that observed in other countries, such as the USA, which is characterized by lower amounts of cereals and legumes and higher amounts of meats, eggs, and dairy products. The food group that made the largest contributions to the energy intake in these Indian women was cereals (64.5 %), a value more than twice the~30 % of total energy coming from cereals in the usual American diet [41]. The high cereal content of the diet of Indian women also contributes the highest amount of protein (also 64.6 %) while meat, fish, poultry, and eggs only contributed 5.6 % of protein intakes; in contrast, cereals contributẽ 15 % and meat, fish, poultry, and eggs~43 % to total protein intake in the USA [41].…”
Section: Discussionmentioning
confidence: 99%
“…This dietary pattern is very different from that observed in other countries, such as the USA, which is characterized by lower amounts of cereals and legumes and higher amounts of meats, eggs, and dairy products. The food group that made the largest contributions to the energy intake in these Indian women was cereals (64.5 %), a value more than twice the~30 % of total energy coming from cereals in the usual American diet [41]. The high cereal content of the diet of Indian women also contributes the highest amount of protein (also 64.6 %) while meat, fish, poultry, and eggs only contributed 5.6 % of protein intakes; in contrast, cereals contributẽ 15 % and meat, fish, poultry, and eggs~43 % to total protein intake in the USA [41].…”
Section: Discussionmentioning
confidence: 99%
“…The National Health and Nutrition Examination Survey of the USA, although adopting a different approach for food grouping, reported that energy-dense and nutrient-poor foods/beverages comprised at least 36 % of the total energy intake of US adults (27) . The National Diet and Nutrition Survey of the UK did not provide separate analysis for discretionary foods/beverages but did recognize the large and constant contribution of food intakes from unhealthy choices including hot chips, processed meat, confectionery and soft drinks among adults from 2000 to 2009 (28) .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, data obtained from 7873 adults (19 years or above) with at least one 24 h dietary recall and weight and height measured were used for analyses, with the results weighted to reflect the Australian population (5)(6)(7) . Age groups were based on the NNPAS age categories (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), 51-70 and 70+ years) and socio-economic quintiles were based on the Socio-Economic Index of Disadvantage for Areas (SEIFA), where the first SEIFA quintile indicates the most disadvantaged areas (5) . Country of birth was classified according to whether the respondents were born in Australia, English-speaking countries, or others.…”
Section: Anthropometry and Demographic Characteristicsmentioning
confidence: 99%
“…An additional serving of dairy may be one approach to help Americans get more magnesium since increasing dairy from current to recommended amounts reduced the percentage of people below the EAR by as much as 26 %. Based on current dietary intakes, milk is the primary contributor of magnesium to the diet of children 3 and the second highest contributor for adults 4 in the U.S. compared to other foods. Other magnesium-rich foods such as nuts and beans should also be considered to help fully close this nutrient gap (1).…”
Section: Other Vitamins and Mineralsmentioning
confidence: 99%